2011
DOI: 10.4028/www.scientific.net/amr.295-297.929
|View full text |Cite
|
Sign up to set email alerts
|

Differential Scanning Calorimetry (<i>DSC</i>) Analysis of Abaca Fibre (<i>Musa Textile Nee</i>) Reinforced High Impact Polystyrene (<i>HIPS</i>) Composites

Abstract: Differential scanning calorimetry (DSC) was used to study the thermal behaviour of abaca fibre reinforced high impact polystyrene (HIPS) composites. Thermal analysis is based upon the detection of changes in the heat content (enthalpy) and the glass transition temperature (Tg) of optimum condition of abaca fibre reinforced HIPS composites. In this research, glass transitions temperature (Tg) of neat HIPS occurred below the Tg of optimum condition of composites as the temperature of an amorphous state. The endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…The HIPS curves showed a single stage of mass loss at approximately 444.88 °C, which is also the level observed in the works of Cordeiro et al [37] and Agung et al [38] ; in this case 415 °C. The curves of the composites showed that the addition of the residue provided a slight increase in the temperature at the beginning of degradation of the M2.5 composite, i.e., 444.68 °C (Figure 6c), but for the M5 composite this temperature dropped to 275.94 °C (Figure 6d).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The HIPS curves showed a single stage of mass loss at approximately 444.88 °C, which is also the level observed in the works of Cordeiro et al [37] and Agung et al [38] ; in this case 415 °C. The curves of the composites showed that the addition of the residue provided a slight increase in the temperature at the beginning of degradation of the M2.5 composite, i.e., 444.68 °C (Figure 6c), but for the M5 composite this temperature dropped to 275.94 °C (Figure 6d).…”
Section: Resultssupporting
confidence: 87%
“…Figure 7 also shows the specific heat (Cp) reduction for composites. This behavior was caused by the shells, which reduced heat transfer [38] . The shells of Brazil nuts consist of the exotesta regions, central mesotesta region, mesotesta vascular region and tegmen that present structures with voids such as long and porous cells, porosities and vascular exchanges [41,42] .…”
Section: Resultsmentioning
confidence: 99%
“…DCS was carried out to determine the thermal behaviour of the fibers. DSC analysis also enables the identification to be made of chemical activity occurring in the fibers as the temperature is increased (Agung et al 2011). Figure 4a shows the DSC curve for raw kenaf bast fiber.…”
Section: Thermal Analysismentioning
confidence: 99%